Pengaruh Pemberian Core Stability Exercise Dan Latihan Shuttle Run Terhadap Peningkatan Agility Pemain Futsal - Ramadan, Fachrurrozi, Agus Widodo, S.Fis, M.Kes (2017)
Background: Futsal is a fast game with a short time and the space is cramped. So that in a game of futsal required agility. In an effort to increase agility, exercise should out carefully, systematically and regulary. This study aims to determine the increase agility futsal players through core stability exercise and shuttle run training. Research Objective: To determine the effect of core stability exercise and shuttle run to the improvement agility of futsal players. Research Methods: This type of research is an experimental research design with Pre and Post Test Two Group Design. The population in this study is Tambusai FC futsal players who totaled 16 people. Results: Normal distribution of data and homogeneous variance, hypothesis testing on core stability exercise using Paired Sample T-Test with tvalue of 28,333 Sig (p value) 0,000 is smaller than 0,05 (0,000 <0,05) means there agility increased influence of futsal players. And the shuttle run with tvalue of 36,425 with Sig (p value) 0,000 is smaller than 0,05 (0,000 <0,05) means that there is the effect of an increase in agility. To test the effect of different uses Independent Sample T-Test with tvalue of -10.888 with Sig (p value) 0,000 smaller than the level value of 0,05 (0,000 <0,05) means that there are differences in the effect of core stability exercise and shuttle run to increase agility futsal players. Conclusion: Core stability exercise and shuttle run can improve agility futsal players. But the provision of shuttle run is more effective in improving agility than core stability exercise. Keywords: core stability exercise, shuttle run, agility, futsal players.